1994
DOI: 10.1002/art.1780370306
|View full text |Cite
|
Sign up to set email alerts
|

A Cost‐Utility Analysis of Misoprostol Prophylaxis for Rheumatoid Arthritis Patients Receiving Nonsteroidal Antiinflammatory Drugs

Abstract: Objective. To determine the cost-utility of lowdose misoprostol prophylaxis in rheumatoid arthritis (RA) patients treated with nonsteroidal antiinflammatory drugs (NSAIDs).Methods. Prospectively collected, populationbased data on 57 RA patients' preferences (obtained using the category scaling and time trade-off techniques), charge data from a consecutive, populationbased cohort of 36 RA patients with NSAID-related gastric ulcer, and literature-derived probability estimates were incorporated into a decision an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 57 publications
0
25
1
1
Order By: Relevance
“…Three studies reported cost-utility analyses. 12,156,170 Sixteen studies carried out costeffectiveness analysis where they incorporated probabilities into a decision-analytic model, but did not report ICERs, just expected costs.…”
Section: Type Of Economic Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported cost-utility analyses. 12,156,170 Sixteen studies carried out costeffectiveness analysis where they incorporated probabilities into a decision-analytic model, but did not report ICERs, just expected costs.…”
Section: Type Of Economic Analysis Methodsmentioning
confidence: 99%
“…Resource use associated with treatment pathways was obtained using expert opinion in 17 studies, 15,149,150,155,157,158,[160][161][162][163][165][166][167][168]173,175,176 patient records in five studies, 11,154,156,160,177 insurance or hospital billing in five studies, 13,157,172,174,179 national or diagnosis related group (DRG)-linked reimbursement in four studies 159,164,171,180 and was not reported in five studies. 12,153,169,170,178 …”
Section: Sources Of Resource Use and Cost Datamentioning
confidence: 99%
“…81,[117][118][119][120][121][122][123][124][125] Several published economic analyses of drug therapies for use in RA were also identified, relating to the use of NSAIDs, for example, see Gabriel and colleagues 126 and DMARDs. [127][128][129][130] No fully published economic evaluations of anakinra treatment for patients with RA were identified from the literature.…”
Section: Existing Economic Evaluationsmentioning
confidence: 99%
“…Although a number of authors have begun to emphasize the advantages of adopting a Bayesian perspective in probabilistic modeling, [27][28][29] many probabilistic analyses do not adopt a Bayesian approach, and for such studies the choice of distributions to represent uncertainty in parameters may appear rather ad hoc. [30][31][32][33][34][35][36] Furthermore, the Bayesian approach may afford a more intuitive interpretation of the probabilistic sensitivity results that has been highlighted as lacking in a review of the use of medical decision analysis models. 37 Adopting a Bayesian approach to the probabilistic analysis of the model of GERD management allows the intuitive interpretation often afforded to acceptability curves as showing the probability that the intervention is cost-effective.…”
Section: Discussionmentioning
confidence: 99%